The India-China-USA Triangle in South Asia and Russia - S. I. Lunev; A. Yu. Davydenko (Сравнительная политика, 2025)
The article examines the transformation of South Asia, highlighting the distinctive characteristics of the foreign policy strategies of major powers, the interplay between regionalization and globalization, and the prospects for either confrontation or interdependence among the region’s dominant states. South Asia is currently undergoing multifaceted and ambiguous repercussions of significant geopolitical shifts, underscoring the growing importance of analyzing the contemporary phase of interstate relations in this region. South Asia, in many ways, mirrors the broader global changes but on a smaller scale. The region comprises countries with stark disparities in territory, population, economic capacity, scientific and technological advancement, military power, as well as cultural and civilizational traits – all of which significantly shape interstate relations. India’s dominance within the region fosters distrust among its neighbors and exacerbates their perception of vulnerability. Consequently, these states increasingly seek to strengthen their positions in both regional and international arenas by leveraging relationships with extra-regional powers, most notably China. Moreover, unresolved disputes with India are frequently brought to the attention of the international community. The article also addresses the impact of external factors on South Asia’s international relations system, focusing on the substantial shifts in the strategies of major powers following the Cold War. It explores key issues such as the Indian-Chinese rivalry in the region, the United States’ adverse influence, and Russia’s policy toward South Asia.